In vitro antioxidant and cytotoxic potential of Eclipta prostrata L. aerial part extracts - Minh, Phan Hong; Yen, Ta Phuong; Ngoc, Tran Thi Hong; Tuan, Le Anh; Huong, Nguyen Thuc Thu; Thanh, Mai Phuong (Tạp chí Nghiên cứu Y học, 2025)
The phytochemical exploration in medicinal plants is increasingly recognized for its diverse pharmacological benefits. This research aims to evaluate the antioxidant potential and anticancer properties of Eclipta prostrata L. (EPL) extracts on human breast adenocarcinoma (MCF7), hepatocellular carcinoma (HepG2), and human gastric carcinoma (MKN-7) cell lines. The dried plant material was extracted in 70% ethanol, n-hexane, ethyl acetate, and n-butanol solvents. The antioxidative properties of EPL extracts were assessed through ABTS and FRAP assays, while the antiproliferative effects were measured using the sulforhodamine B assay. Findings indicated that the ethyl acetate extract exhibited higher antioxidant and cytotoxic activities against the HepG2 cell line compared to other extracts. Future research should aim to isolate and characterize the specific bioactive compounds responsible for the observed anticancer and antioxidant effects, and clarify their mechanisms of action.